Designing ecologically-inspired robustness into a water distribution network. (1st May 2020) - Dave, Tirth; Layton, Astrid
Abstract: Eco-Industrial Parks (EIPs), network of industries that collaborate by utilizing each other's byproducts and wastes, are highly desirable for both the industries themselves, their environment, and governments due to their economic, environmental, and social advantages. Previous work has shown that EIPs are not as successful as they could be in terms of mimicking the behavior of biological ecosystems, highlighting that more work needs to be done for EIPs to truly mimic their biological-counterparts. The Kalundborg EIP, located in Kalundborg, Denmark, is a well documented example of an EIP with long-term success. Using the water network within the Kalundborg EIP as a case study, two bio-inspired networks are selected from an optimization based on the ecosystem metric robustness . The bio-inspired solutions are compared with a traditionally cost-minimized solution to understand what bio-inspired design can offer when a network is disturbed. Disturbances such as connection breakages and industry shutdowns are tested, showing that the bio-inspired designs require minimal recovery costs – in stark contrast to the traditional network solution. The results show that the bio-inspired designs reduce the network's dependence on a scarce import (freshwater) and have higher overall network resilience in the event of disturbances. The three network solutions are discussed from a ecological perspective, explaining differences from the standpoint of ecosystem characteristics. The analysis highlights the benefits of using ecology to understand the nature of and improve the design of industrial networks. Highlights: Mimicking ecological food webs creates sustainable water network. Optimizing ecological robustness uniquely balances cost and resiliency. Bio-inspired water network are cost effective under disturbances. Ecological robustness also increases value cycling in distribution networks.